A blind image watermarking scheme combining spatial domain and frequency domain - Yuan, Zihan; Su, Qingtang; Liu, Decheng; Zhang, Xueting (The Visual computer, 2021)
In order to realize the copyright protection of color image effectively, combining the advantages of spatial-domain watermarking scheme and frequency-domain one, a blind color image watermarking scheme with high performance in the spatial domain is proposed in the paper. The presented scheme does not require real discrete cosine transform (DCT) and discrete Hartley transform (DHT), but only uses the different quantization steps to complete the embedding and blind extracting of color watermark in the spatial domain according to the unique characteristic of direct current (DC) components of DCT and DHT. The contributions of this paper include the following: (1) This scheme combined the strengths of watermarking scheme in the spatial domain and frequency domain, which has fast speed and strong robustness; (2) the scheme makes full use of the energy aggregation characteristics of image block, and the invisibility of the watermarking scheme has greatly improved; and (3) different quantization steps are chosen to embed and extract watermark in different layers, which reduce the modification range of pixel value effectively. The experimental results show that compared with the existing schemes, the proposed watermarking scheme has higher performance, such as better invisibility, stronger robustness and shorter execution time.